In situ imaging of biopolymers and extracellular enzymes in activated sludge flocs of a municipal wastewater treatment plant - Szilveszter, Szabolcs; Ráduly, Botond; Ábrahám, Beáta; Lányi, Szabolcs (Journal of chemical technology and biotechnology (1986), 2013)
BACKGROUND The aim of this study was to investigate biopolymers and extracellular enzymes in whole activated sludge flocs originating from a full‐scale wastewater treatment plant, by means of confocal laser scanning microscopy (CLSM) techniques. Both sectioned and whole activated sludge floc samples have been stained using specific fluorochromes and immunostains in order to visualize the structural and functional characteristics of these bioaggregates. Samples were stained for visualization of lipids, sugars, total cells, esterase enzyme producing bacteria, and for β‐glycosidase (EC3.2.1.21), alkaline phosphatase (EC3.1.3.1) and trypsin (EC3.4.21.4) enzymes. Simultaneous staining schemes were applied and immunostaining specificity tests were performed. RESULTS By the CLSM imaging and the 3‐D reconstruction of the stained flocs the distributions of the targeted floc components were successfully assessed. The immunostain specificity controls gave satisfactory results in each case. The reflected total cells‐to‐enzymes ratio was repeatedly higher for the sectioned samples. CONCLUSIONS The CLSM imaging of whole sludge flocs delivers valuable information on the spatial distribution of the floc build‐up materials, with a satisfactory visualization accuracy of the individual components. The images of whole and sectioned samples showed similar distributions of the floc components, but the consistent differences revealed in cells‐to‐enzymes ratios call for further research.© 2012 Society of Chemical Industry